Back Cover, Volume 132, Issue 21. Issue 21 (5th June 2015) - Escobar, Isabel C.; Van der Bruggen, Bart
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> Polysulfones (PSUs) have been the basis of several applications, for example microfiltration membranes, gas separation, fuel cells and drug delivery. However, a drawback for the application of PSU membranes is their intrinsic hydrophobicity which causes fouling. To improve fouling resistance, hydrophilic functional groups can be bonded to the PSU's backbone. Yihui Xie, Russell Tayouo and Suzana Pereira Nunes modify PSU in different degrees of functionalization by using a well‐known click reaction, the copper(I)‐catalyzed azide‐alkyne cycloaddition between an organic azide and a terminal alkyne. The cover shows the morphology of a cross section of a membrane prepared by phase inversion in water. (DOI: 10.1002/app.41549)